Development of ureasil-polyether membranes for guided bone regeneration - Oshiro, Joao Augusto [UNESP]; Scardueli, Cassio Rocha [UNESP]; Pimentel Lopes de Oliveira, Guilherme Jose [UNESP]; Chierici Marcantonio, Rosemary Adriana [UNESP]; Chiavacci, Leila Aparecida [UNESP] (Iop Publishing Ltd, 2017)
The aim of this study was to develop a new barrier membrane from ureasil-polyether hybrid materials for guided bone regeneration. The membrane was prepared via the sol-gel route by using polyethylene oxide and polypropylene oxide polymer blends; dexamethasone was used as a drug model for in vitro release testing. Membrane swelling was monitored by small-angle x-ray scattering (SAXS) measurement and bone formation was investigated by microtomography. In vitro drug release testing revealed sustained profiles that could be controlled by varying the proportions of the polymers. SAXS analysis showed that the polymer blend can control the high swelling observed when using ureasilpolyethylene oxide material. Histological results revealed that the ureasil-polyether blend promoted local inflammation similar to the response caused by commercial collagen membrane. The results of microtomography showed that the osteo-regeneration of bone defects by using ureasil-polyether membranes was similar to the effect promoted by commercial collagen membrane. These results indicate that ureasil-polyether membranes are promising candidates for barrier membrane, considering their low cost, luminescence, control of drug release, ease of handling, and biocompatibility.
Keywords: ureasil-polyether hybrid materials; sol-gel process; membranes; guided bone regeneration